Digital technologies and interdisciplinarity in the teaching of human physiology (Revista Contexto & Educação, 2023)
The objective is to analyze how Digital Information and Communication Technologies (DICTs) contribute to the understanding of public high school students about Human Physiology from interdisciplinary Biology and Physical Education classes. Faced with the problem of fragmentation of knowledge and the application of expository methodologies in the teaching process of Human Physiology content, exploratory qualitative research was developed, with the participation of seventeen students, during August to October 2019. The research subdivided into three phases: planning, data collection, and analysis. The collections were made from an evaluative questionnaire, video production featuring Digital Educational Authorial Material (DEAM), application of a posteriori questionnaire. Data analysis was performed in an interpretative manner with an emphasis on two focuses: the establishment of relationships between the concepts of blood pressure and exercise physiology; facilities and difficulties in establishing these relationships. The study demonstrated the presence of conceptual additions by students: understanding of the human circulatory system, the role of blood pressure in the body, and the role of hormones in responses to external stimuli. The construction of knowledge itself proved to be an important way to make learning more meaningful.
Keywords: Digital Technologies; Interdisciplinarity; Human Physiology; Digital Educational Authorial Material.